“I Am Eighteen, Why Am I Inside Here?”. A Reflection Upon the Detention and Criminalisation of Migrants under Italian Administrative Law (AmeriQuests, 2014)
This article analyses the evolution in Italian migration law relating to immigration detention with the purpose of demonstrating the incompatibility of administrative detention with the European human rights framework and the fundamental principles of the Italian constitutional and administrative law. The authors make reference to first-hand testimonies from their own prior interview-based research into Turin’s immigration detention centre; a case study which is symptomatic of systemic issues found throughout the Italian administrative detention system. By reflecting upon the practical application of the law, the article demonstrates that immigration detention intentionally ignores many of the philosophical underpinnings of the Italian administrative law system. Moreover, immigration detention illustrates the discrepancies between the administrative and criminal judicial systems, as third-country nationals who risk losing their liberty due to administrative detention do not have access to the same procedural safeguards and rights protection which are guaranteed to those who risk losing their liberty due to alleged criminal conduct. The Italian case study raises broader questions as to whether the administrative detention system might be accurately described as an “illegality regime” as defined by Amaya-Castro (2011); this article explores whether it might be apt to differentiate the notion of illegality regime with a new concept of “un-legality regime”.
Keywords: immigration detention; human rights; criminalisation of migrants; CIE